Lethocerus patruelis (Stål, 1855) in Italy: a recent introduction or a natural westward spread? (Hemiptera: Heteroptera: Nepomorpha: Belostomatidae) - Cianferoni, Fabio; Nardi, Gianluca (Zootaxa, 2013)
The paper provides new records and a critical review of the previous citations of Lethocerus patruelis (Stål, 1855) from Italy. The status of the species in Italy, and whether its presence can be related to a recent introduction or to a natural west-ward spread, is discussed, but further observations are needed to assess its effective status in the country. The dates of description for this species and of L. niloticus (Stål, 1855) are corrected, since they have up to the present time been incorrectly stated as 1854.